The influence of dietary patterns and sedentary lifestyle on students’ learning outcomes - Mahesha Aulia Indriani; Sapto Wibowo (MEDIKORA, 2025)
This study aims to analyze the influence of dietary patterns and sedentary lifestyle on the learning outcomes of tenth-grade students at SMAN 1 Driyorejo. The study employed a quantitative approach with a correlational research design to examine the relationships and effects among the variables. The sample consisted of 35 students from class X-11 selected through purposive sampling. Research instruments included questionnaires on dietary patterns, sedentary lifestyle behavior, and documentation of students’ academic achievement. The collected data were analyzed using instrument validity testing, descriptive statistical analysis, Pearson correlation analysis, t-test, and multiple linear regression analysis. The results indicate that dietary patterns have a positive and significant effect on students’ learning outcomes, while sedentary lifestyle shows a significant influence with a tendency to reduce academic performance. Furthermore, the regression analysis reveals that dietary patterns and sedentary lifestyle simultaneously contribute significantly to variations in students’ learning outcomes. These findings emphasize that balanced nutritional intake and adequate physical activity play an important role in supporting students’ concentration, learning stamina, and academic performance. Therefore, improving dietary habits and reducing sedentary behavior are essential strategies for enhancing students’ learning outcomes in the digital era.